MENGUKUR KINERJA KEUANGAN PT MITRA ADIPERKASA (Tbk) Periode 2022 – 2024 - Hamizar Hamizar (POLITEKNIK LP3I JAKARTA, 2025)
This study aims to measure the financial performance of PT Mitra Adiperkasa Tbk in the period 2022-2024 by comparing it to PT Ramayana Lestari Sentosa Tbk through a financial ratio analysis approach that includes liquidity, solvency, profitability, and activity ratios. In addition, a measurement of the level of financial health was carried out based on the Decree of the Minister of SOEs No. KEP-100/MBU/2002. The data collection technique uses a Decision study from various reference sources to gain a better understanding, in addition to using secondary data collection techniques through official websites such as TICMI (The Indonesia Capital Market Institute). The results of the financial performance analysis of PT Mitra Adiperkasa Tbk in 2022-2024 based on the liquidity ratio analysis show that PT Mitra Adiperkasa Tbk is in a liquid condition. The solvency ratio analysis shows unhealthy financial performance because the Debt to Asset Ratio and Debt to Equity Ratio values ​​for three consecutive years are above the ideal limit. The activity ratio analysis shows suboptimal performance in utilizing owned assets. Profitability analysis shows a tendency to decline, reflected in the Net Profit Margin, Return on Investment, and Return on Equity which have weakened from year to year. The results of the PTBA Health Level analysis according to the decision of the Minister of SOEs PT Mitra Adiperkasa Tbk are in the unhealthy category (BBB) ​​in 2023 and 2024 after experiencing healthy performance (A) in 2022.